Development of an Interval Scale of Anxiety Response - Corah, Norman L. (1986)
This paper reports the development of an interval scale of anxiety response. Magnitude estimation procedures were used with three different groups of subjects to develop a suitable scale of seven anxiety descriptors. The ratio of the highest to lowest descriptor magnitudes was 21 to 1. Analyses of the descriptor sets in the various groups indicated high reliability of meaning and high objectivity. In addition, high agreement on meaning was shown for groups of differing education and socioeconomic status. A preliminary study using the scale indicates appropriate preliminary construct validity. Further reliability and validity research is needed. This scale may be useful for assessing anxiety response changes in a variety of contexts.